Corporate social responsibility and education reform in Brazil: a critical analysis (2019)
This chapter uses the case of the Intel Corporation in Brazil to explore the tensions surrounding the use of corporate funding to promote education reform, making two main contributions to the field of philanthropy in education. First, it adds to the work that has been done by Ball (2012) and other scholars (Peck & Theodore, 2012; Urry, 2003) towards exploring policy-making outside traditional channels and investigating the structures and nuances of these under-explored ‘globalising micro-spaces’. Second, it devotes significant attention to the question of whether it is possible for corporations to make long-term and systemic contributions to the field of education.